What We Think We Are: Maximizing the Subjects in the Human Sciences. - FLEMING MILLER, Lantz (Annals of Philosophy, Social & Human Disciplines, 2022)
The human sciences, differ from the natural in significant ways. The complexity of subject matter may be to blame. Bases of controlled experiments differ, some humansubjects research hard to control, and there are moral constraints on what can be done to a human research-subject. Human-science subjects have a peculiar trait: Subjects' concepts concerning themselves play into what they are, even if some such concepts are false. The human sciences, in their struggle for objectivity, often commonly have allowed only limited role for subjects' concepts about themselves. This article contends that a significant amount of peoples' ideas and theories do influence their behavior - and most significantly, those ideas about themselves or reflexive concepts. Taking into account subjects' ideas of themselves appears to be needed in much human-sciences research to maximize study accuracy and completion.